Apprentissage social affectif et appréciation de l'émotion: structuration des interactions socioémotionnelles - Dukes, Daniel (My University, 2018)
This paper highlights a novel concept that focuses on obtaining knowledge through the observation of others. In the same way as social learning is concerned with learning from others how to use objects in the environment through various forms of imitation, what we have called 'affective social learning' is concerned with learning how to value objects in the environment through the emotional expressions of others. This paper also looks to highlight the importance of taking a relational view of emotion recognition – what I have called emotion appreciation. This concept offers a more holistic approach than just focusing on facial emotion recognition and, in my opinion, is more likely to help the infant or the newcomer understand how to value the objects in their new environment.